Bimbel Activities Program Guide Using Collaborative Approach of School Elementary Student at Village Pajintan - Citra Utami; Zulfahita Zulfahita; Buyung Buyung; Evinna Cinda (International Journal of Public Devotion, 2018)
Free Tutoring Program conducted by lecturers collaborate with students STKIP Singkawang seeing their children's needs will be additional learning after school. Tutoring helps students in doing homework on a given subject in school and help the students' understanding of the lessons they do not understand at school. In addition to assisting students in understanding cognitive activities, tutors also inculcate moral values are good to the students as a way to talk, behave towards older people and others. Tutoring also helps faculty to see the education of elementary school children in pajintan and tutors teach students to develop their abilities in front of the children as their stock later after becoming a teacher. Tutoring activity is carried out twice a week is Saturday and Sunday at 15: 00-16: 030. Kids will get together and tutor will ask them what they learned today. Then divide each tutor will be in accordance with the appropriate number of students and subjects what they want to learn. The number of students in the activities is 26 students tutoring kids who follow learning have willingness to learn. Results are expected after tutoring activities are the students who are expected to gain new knowledge or mastery of a better school after attending tutoring